United we stand : the role of spirituality in engaging and healing communities - Davis, Dannielle Joy, 1974- (Contemporary perspectives on spirituality in education., 2020)
"Segments of society are drawing upon their faith and spirituality to develop strategies to mend social relationships and fragmented communities. The Contemporary Perspectives on Spirituality in Education book series will feature volumes geared towards understanding and exploring the role of spirituality in addressing challenge, conflict, and marginalization, particularly within education in the U.S. and internationally"--